A fast, single column extraction chromatography method for the isolation of neodymium from iron-rich materials prior to radiogenic isotope ratio measurements. Issue 1 (14th December 2021) - Gannoun, Abdelmouhcine; Suchorski, Krzysztof; Pin, Christian
Abstract : A novel separation method is described for the separation of Nd from Fe-rich, silicate samples in view of isotopic analyses. Abstract : A novel separation method is described for the separation of Nd from Fe-rich, silicate samples in view of isotopic analyses. The procedure is based on the synergistic enhancement of the extraction of the REE from HCl media by the diglycolamide ligand in the presence of large amounts of Fe(iii ). Following sample decomposition with a mixture of HF and HCl, the resulting, ca. 4 M HCl solution is immediately loaded on a column of DGA resin, without evaporation of HF and volatilization of silicon. Both Fe(iii ) and the REE are extracted by the resin while most other elements pass through the column. Then, iron is stripped from the column with 3 M HNO3 . Finally, the LREE are eluted sequentially by means of HCl of decreasing strength, thereby providing a Nd fraction suitable for isotope ratio measurements by MC-ICP-MS. Because it does not require evaporation steps, this method offers a robust, straightforward alternative to more complicated schemes when samples unusually rich in iron are to be analysed. The potential of this protocol is demonstrated by several replicate analyses of two Fe-rich international SRMs, namely the banded iron IF-G (56 wt% Fe2 O3 ) and the bauxite BX-N (23% Fe2 03 ).